Megakaryocyte Polyploidization and Proplatelet Formation in Low-Attachment Conditions - Schlinker, Alaina C (Biochemical engineering journal, 2016)
In vitro-derived platelets (PLTs), which could provide an alternative source of PLTs for patient transfusions, are formed from polyploid megakaryocytes (MKs) that extend long cytoplasmic projections, termed proplatelets (proPLTs). In this study, we compared polyploidization and proPLT formation (PPF) of MKs cultured on surfaces that either promote or inhibit protein adsorption and subsequent cell adhesion. A megakaryoblastic cell line exhibited increased polyploidization and arrested PPF on a low-attachment surface. Primary human MKs also showed low levels of PPF on the same surface, but no difference in ploidy. Importantly, both cell types exhibited accelerated PPF after transfer to a surface that supports attachment, suggesting that pre-culture on a non-adhesive surface may facilitate synchronization of PPF and PLT generation in culture